Pengaruh Jumlah Desa Wisata dan Jumlah Kunjungan Wisatawan Desa Wisata Terhadap Pendapatan Asli Daerah di Provinsi D.I. Yogyakarta - Jurni Hayati (Convergence: The Journal of Economic Development, 2021)
This study aims to see how the influence of the number of tourist villages and the number of tourist village visits on local revenue in the Province of D.I. Yogyakarta. The data used in this study is secondary data for 2016-2020 obtained from BPS D.I. Yogyakarta. The analysis used is multiple linear analysis with the help of the eviews 10 application. Based on the results of the analysis of the number of tourist villages and the number of tourist visits to tourist villages simultaneously, there is no significant effect on local revenue in the Province of D.I. Yogyakarta. Partially, the variable number of tourist villages has a significant effect on local revenue in the Province of D.I. Yogyakarta, while the variable number of tourist visits to tourist villages has no significant effect on local revenue in the Province of D.I. Yogyakarta.